(q-3)*5=15

Simple and best practice solution for (q-3)*5=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (q-3)*5=15 equation:


Simplifying
(q + -3) * 5 = 15

Reorder the terms:
(-3 + q) * 5 = 15

Reorder the terms for easier multiplication:
5(-3 + q) = 15
(-3 * 5 + q * 5) = 15
(-15 + 5q) = 15

Solving
-15 + 5q = 15

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 5q = 15 + 15

Combine like terms: -15 + 15 = 0
0 + 5q = 15 + 15
5q = 15 + 15

Combine like terms: 15 + 15 = 30
5q = 30

Divide each side by '5'.
q = 6

Simplifying
q = 6

See similar equations:

| 10x-8=9x+6 | | sen*6x+cos*4x+sen*4x+cos*6x=0 | | -2a=-9 | | x^4-3x^3-2x^2-2x+12=0 | | -11+7m+16+(-9m)= | | (-7x-4)(2x+8)= | | 2ln(x)+2x^2+7=0 | | 14x=14x+12 | | 2(x+1)=-3x-10 | | 4x-2(x+1)= | | 4x-12=28-x | | Y=-3.8x+7.1 | | 7v+27=-5(v-3) | | 420t-6t^2=3675 | | 3a*2+yx=7 | | 6(x-4)=8x-28 | | 4*(x+1)=2*(5-3x) | | 6+3a= | | 7u-36=3(u-8) | | t^2-60t=-450 | | t^2+60t=-450 | | -3*-3+6+2= | | 14(6x+16)= | | 3*3+6+2= | | 5+7(2b-2b)=5 | | y(25+-.75y)=350 | | x^2+y^2+6x-14y+42=0 | | 42-21x=63-7y | | (6xy+7)dx+(3x^2-2)dy=0 | | 6x+9-x+19= | | 4x+10=-42-8x | | 3n=34 |

Equations solver categories